2015
DOI: 10.1039/c5cc04901f
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal labelling of living bacteria using unnatural amino acids containing nitrones and a nitrone derivative of vancomycin

Abstract: Unnatural D-amino acids bearing endocyclic nitrones were developed for live-cell labelling of the bacterial peptidoglycan layer. Metabolic incorporation of D-Lys and D-Ala derivatives bearing different endocyclic nitrones was observed in E. coli, L. innocua, and L. lactis. The incorporated nitrones of these bacteria then rapidly underwent strain-promoted alkyne-nitrone cycloaddition (SPANC) reactions affording chemically modified bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…The highly reactive tetrazine and TCO scaffolds can be used by pairing them with smaller, alternative reactive tags. We have previously shown that nitrones are small enough to be tagged onto unnatural amino acids (UAAs) and glycans, which are then readily taken up into the peptidoglycan wall and cell membrane, respectively . As the UAAs bearing nitrones proved to be stable and demonstrated robust incorporation, our work expands the bioorthogonal labelling toolbox to incorporate fluorophores bearing a s‐TCO moiety.…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations
“…The highly reactive tetrazine and TCO scaffolds can be used by pairing them with smaller, alternative reactive tags. We have previously shown that nitrones are small enough to be tagged onto unnatural amino acids (UAAs) and glycans, which are then readily taken up into the peptidoglycan wall and cell membrane, respectively . As the UAAs bearing nitrones proved to be stable and demonstrated robust incorporation, our work expands the bioorthogonal labelling toolbox to incorporate fluorophores bearing a s‐TCO moiety.…”
Section: Methodsmentioning
confidence: 90%
“…Nitrones have been shown to be excellent 1,3‐dipoles as they react with a number of bioorthogonal partners, and demonstrate rates faster than the parallel reactions with azides . Moreover, cyclic nitrones have the advantage of providing additional sites for manipulating strain and electronics, and are stable under both acidic and basic aqueous conditions . Similar to cyclopropenes and azides, nitrones are small and can overcome issues of diene size, hydrophobicity and stability; factors limiting the use of tetrazines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] Nitrone-modified biomolecules have been applied to sitespecific modification of proteins [8] and labeling of mammalian cell surfaces [9] and bacterial cell walls. [10] Second, C = N isomerization is known to provide af acile non-radiative deactivation pathway for fluorescent [11] and phosphorescent [12] compounds.T hus,w hen the isomerization of the C= Ng roup is inhibited, these compounds are expected to resume their emission behavior. To our knowledge,n itrone derivatives have never been explored for the construction of bioorthogonal probes.…”
mentioning
confidence: 99%